Redenomination Doesn’t Change the Purchasing Power of People, but Social Habits - Joesoef, Jose Rizal; Sulistiyanti, Sulistiyanti (oneamd.com, 2025)
Bank Indonesia has been introducing its plan to implement the redenomination of Rupiah by reducing the nominal value (or the face value) of Rupiah from 100.000 to 100, from 50.000 to 50, from 20.000 to 20, from 10.000 to 10, from 1.000 to 1 and so on. It means that the rate of redenomination is 1/1000 (thousandth). As long as the redenomination of Rupiah is implemented simultaneously with obligating people to rescale all prices of commodities in all markets at the same rate (1/1000), the potential pressure of inflation can be pushed down. At the same rate means that both buyer’s monies and seller’s prices are divided by 1.000. It is expected that the redenomination will bring out new social habits in expressing and quoting any value accounted with the unit of Rupiah. People will have to express hundreds of Rupiahs instead of hundreds of thousand, tens of Rupiahs instead of tens of thousands and just rupiahs instead of thousands. They will have to relearn how to write, read, and put numbers after the comma. A discussable definition or the denotative meaning is proposed here, that is, the redenomination is the simplification and equalization in quoting and presenting the nominal value of Rupiah, by dividing all units of Rupiah with the numeral 1.000, without changing the purchasing power of the people. This paper recommends to let the word “redenomination” become a new vocabulary in daily conversations. This is to hinder the emergence of connotative meanings (of redenomination) that may divert people away from the correct meaning